2016
DOI: 10.1080/10691898.2016.1196064
|View full text |Cite
|
Sign up to set email alerts
|

Café Data 2.0: New Data From a New and Improved Café

Abstract: In this article, we revisit the caf e story first introduced in 2011. Recent data from this caf e run by business students at a Midwestern public university are explored and analyzed. The data were collected using a point-of-sale system over a 3-month period during the spring semester of 2015. These data can be used in introductory statistics courses to illustrate the use of time series and forecasting, applications of data mining and visualization, as well as sampling, confidence intervals, and inference usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…In this study, we could not observe the application of the Chi-square statistic with the continuity correction factor. This situation is similar to other studies that propose activities to work the Chi-square tests with students [61][62][63][64]. For example, Gibbs and Goossens [64] talk about the relevance of the continuity correction factor and that it is usually not used when working with software because some (e.g., Minitab) do not have the option to use this factor.…”
Section: Final Reflectionssupporting
confidence: 67%
“…In this study, we could not observe the application of the Chi-square statistic with the continuity correction factor. This situation is similar to other studies that propose activities to work the Chi-square tests with students [61][62][63][64]. For example, Gibbs and Goossens [64] talk about the relevance of the continuity correction factor and that it is usually not used when working with software because some (e.g., Minitab) do not have the option to use this factor.…”
Section: Final Reflectionssupporting
confidence: 67%
“…In this sense, diverse authors (e.g., Woodard et al 2020;Fellers and Kuiper 2020;DePaolo et al 2016;Seier 2014;Gibbs and Goossens 2013;Leigh and Dowling 2010), have reported activities or problems proposals with the finality to make more accessible the study of the 2 tests, goodness-of-fit, independence, and homogeneity, which correspond to the problem areas presented in the previous section. However, commonly, in these investigations, the last partial meanings of each problem area (i.e., PM3, PM7 y PM11) were used.…”
Section: Incidence Of Partial Meanings Identified For the Statistical Education Researchmentioning
confidence: 99%
“…An analysis of the activity statement and solution, in terms of the meanings proposed here, allow revealing the primary mathematical objects that correspond to PM11. Another example is that of DePaolo et al (2016), who propose an activity about a sample of 200 transactions, which is solved with the 2 independence test, where primary mathematical objects used (and described) corresponding to PM7.…”
Section: Incidence Of Partial Meanings Identified For the Statistical Education Researchmentioning
confidence: 99%
“…Additionally, we highlight that the prospective teachers did not use the Chi-square statistic with continuity correction as suggested when having small expected frequencies. We have observed this difficulty in research proposing activities to work Chi-square tests with students [55][56][57]. It is very common not to use the continuity correction factor when working with software because some of them (e.g., Minitab) do not have the option to use this factor.…”
Section: Group 3 Of Prospective Teachersmentioning
confidence: 99%